Effects of a Reflection-Integrated CICARE Program on Empathy and Clinical Judgment in Nursing Students: A Quasi-Experimental Study - Qingqing Feng; Min Liu; Tang Tang; Lulu Zhang (Nursing Reports, 2026)
Background/Objectives: Communication training in undergraduate nursing skills courses is often overshadowed by procedural skill acquisition, leaving limited opportunities for students to develop patient-centered communication skills and engage in reflective learning. This study evaluated a reflection-integrated CICARE communication program embedded in a Fundamentals of Nursing skills course and explored students’ learning experiences. Methods: A quasi-experimental study with an embedded qualitative component was conducted among second-year undergraduate nursing students in China. The quantitative component used a non-equivalent control group design, while reflective journals from the Intervention Group provided qualitative data on students’ learning experiences. Two intact classes were assigned to the Intervention Group (n = 65), and two intact classes were assigned to the Control Group (n = 66). The Intervention Group received an 18-week CICARE-based communication program integrated into skills training, including scenario-based role-play, emotional cue recognition, demonstration videos, feedback, and reflective journals. The Control Group received conventional skills training. Outcomes included communication competence, empathy, professional identity, clinical judgment, and course performance. Analysis of covariance was used to compare post-intervention outcomes after adjustment for baseline scores. Reflective journals from the Intervention Group were analyzed thematically. Results: After adjustment for baseline scores, the Intervention Group showed significantly higher communication competence than the Control Group (adjusted mean difference = 2.699, 95% CI: 0.108–5.291, p = 0.041). Empathy was also higher in the Intervention Group (adjusted mean difference = 3.796, 95% CI: 0.538–7.053, p = 0.023). The between-group difference in professional identity was not statistically significant (p = 0.073). The Intervention Group achieved higher total clinical judgment scores than the Control Group (31.52 ± 5.50 vs. 27.20 ± 6.45, p < 0.001), with significant differences in noticing, interpreting, and reflecting. Course performance was also higher in the Intervention Group. In their reflective journals, students described greater patient-centered awareness, attention to patients’ emotional needs, professional reflection, and motivation for self-directed learning. Conclusions: Integrating CICARE-based communication training with reflective learning may strengthen communication competence, empathy, clinical judgment, and course performance in undergraduate nursing skills education. Further studies with longer follow-up are needed to determine whether the observed differences persist over time and whether professional identity and action-oriented clinical responses improve with longer educational exposure. Registration: This study was not registered.